PRESENCIA DE RADIONUCLEIDOS EN ARCILLAS DEL SISTEMA HIDROTERMAL DEL VOLCÁN TURRIALBA, COSTA RICA - García-Vindas, J. R. (2011)
The first results obtained about the presence of radionucleids of terrigenous origin in the hydrothermal system of Turrialba Volcano are shown in this paper. Several samples were taken in the central and southwest craters, and analyzed by gammaray spectrometry, with a Hyperpure Germanium detector. The values ofthe activities of the natural radioactive isotopes are shown in Bq/kg. A disequilibrium in the series of U-238 wasfound, which is explained by two different mechanisms: one convective and the other by Rn222 enrichment. An increase of the activity of all isotopes is observed between September 2001 and May 2002. Because the lowpossibilities that this can be produced by the water runoff, it it proposed that such rise in the concentration ofthe elements can be explained by their presence in the water vapour and other volcanic gases.